PENERAPAN METODE SERVICE LEARNING DALAM PEMBEKALAN ORANG TUA TK SEJAHTERA BANDUNG UNTUK MENDUKUNG KEMANDIRIAN ANAK MENUJU SEKOLAH - Widiastuti, Ratih; Deviana, Tina; Saputra, Dinar; Ghania, Aqila Irza (Universitas Negeri Jakarta, 2025)
The transition from home to school is a crucial stage for early childhood, requiring independence skills, discipline, and the ability to follow instructions. Observations at Sejahtera Kindergarten in Bandung showed that the majority of children aged 3–6 still had difficulty following teacher directions and had not yet demonstrated independent behavior, largely influenced by habits at home. To address this, the community service team conducted a parenting seminar entitled